Analisis Kesiapan Guru dalam Mengembangkan Kemampuan Berpikir Kritis pada Anak Usia 5-6 Tahun di TK Se-Kecamatan Tebing Tinggi Kabupaten Kepulauan Meranti - Rahmadiani, Reni; Nurdin, Zullkiflli; Kurnia, Rita (Universitas Pahlawan Tuanku Tambusai, 2025)
Teacher readiness is an important and decisive factor in achieving learning objectives. Early childhood education (PAUD) teachers must have readiness in the sense of being able and willing to create conditions conducive to effective learning to develop critical thinking skills for early childhood. This study aims to determine the readiness of teachers in developing critical thinking skills for children aged 5-6 years in kindergartens in Tebing Tinggi District, Meranti Islands Regency. This research is quantitative descriptive research. The population in this study were 60 teachers of children aged 5-6 years in kindergartens in Tebing Tinggi District with the sampling technique, namely saturated sampling. The data collection technique used was using a test to determine the teacher's ability and a questionnaire to determine teacher motivation in developing children's critical thinking skills. The data analysis technique used is descriptive statistical analysis. The results of this study revealed that the profile of kindergarten teachers in Tebing Tinggi sub-district mostly had an S1 education level with a percentage of 85%, a length of teaching 0-5 years with a percentage of 35%, and had attended training with a percentage of 55%. Teacher readiness in terms of teacher knowledge in developing critical thinking skills for children aged 5-6 years in Tebing Tinggi District is in the Good category with a percentage of 58%. Teacher readiness in terms of teacher motivation in developing critical thinking skills is in the Good category with a percentage of 95%.